Fabrication of Electrochemical Electrodes Based on Platinum and \(\text{ZnO}\) Nanofibers for Biosensing Applications - Le, Dang Thi Thanh; Hoang, Nguyen Van; Hieu, Nguyen Van; Khue, Vu Quang; Huy, Tran Quang (Communications in Physics, 2017)
Platinum (Pt) electrodes were designed in imitation of screen-printed electrodes, and prepared by microelectronic techniques. These electrodes were then modified with zinc oxide (ZnO) nanofibers for biosensing applications. ZnO nanofibers with average length \( \sim 20-30\; μ\) m and diameter \(\sim 150\) nm in hexagonal crystalline structure are prepared using electrospinning method. Their surface characteristics were analyzed by field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy, and X-ray diffraction. Electrochemical properties of modified Pt electrodes were investigated in comparison with commercial carbon screen-printed electrodes. The results showed that the cyclic voltammogram of modified Pt electrodes was stable, but has much lower resistance compared to that of carbon screen-printed electrodes